Development of a cream containing protocatechuic acid-rich fraction from clinacanthus nutans leaves - Muhammad 'Izzuddin bin Zamery (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2019)
Premature aging is an aesthetic problem that degrades youthful appearance and leads to the lack of one's self-confidence. This may be the reason behind the rocketed sales of the anti-aging and whitening skin care in most of the world markets. One of the common anti-aging bioactives in cosmetics is phytochemicals that possessed antioxidant capacity such as protocatechuic acid, which may be capable of protecting the skin from premature aging due to ultraviolet radiation and free radicals. Therefore, this research was aimed to extract PCA-rich fraction from C. nutans leaves and screened its antioxidant and anti-tyrosinase capacities, to develop the cream containing PCA-rich fraction, and to characterise the developed cream. The extraction processes started with the sequential maceration of dried pulverised leaves of C. nutans with the n¬-hexane as the first in sequence followed by dichloromethane and lastly methanol. Screening of the crude extract for the protocatechuic was done by developing the TLC profiles and compared them to TLC pattern of PCA standard. Since TLC profile of methanol crude extract showed compound with Rf¬ similar to the PCA standard, it had been chosen for further fractionation by vacuum liquid chromatography which yielded 2 g of PCA-rich fraction. PCA-rich fraction had found to have antioxidant and anti-tyrosinase activities as compared to other extracts. As for the development of the cream containing PCA-rich fraction, the development was started with the fabrication of four base cream. Based on the preliminary physical evaluation consisted of odour, colour, texture, homogeneity and spreadability, F4 base cream (placebo) was selected to be incorporated with 1% of PCA-rich fraction to produce PCA cream. Then, characterisation and stability studies were performed for both F4 base cream and PCA cream in accelerated and real-time storage condition for weekly sampling point for one month. The result for the characterisation and stability study showed some of the parameters which were droplet size, zeta potential and pH changed within the period of storage, however, the changes were acceptable since the results were within the acceptance limit. Physical properties and rheological behaviour of the creams were unchanged throughout the period of storage. Microbial limit test also showed negative result in which there were no growth observed in total aerobic microbial count (TAMC), total yeast and mold count (TYMC) and specific microbial tests for Pseudomonas aeruginosa and Staphylococcus aureus. For PCA content in cream analysis, the results showed only a slight insignificant reduction of PCA content in the cream for both accelerated and real-time storage condition. Last part of the research was about the in vitro release study of PCA from the cream by using Franz diffusion cell and silicone membrane as barrier between cream sample and receptor medium. The HPLC analyses showed there was no PCA permeated into the receptor medium. However, PCA had been recovered on the surface of the silicone membrane as well as deposited within the silicone membrane. As a conclusion, protocatechuic acid-rich fraction had been successfully obtained and a cream containing the PCA-rich fraction was successfully developed.